Monetarist Principles and the Money Stock Growth Rule - McCallum, Bennett T. (American Economic Review, 1981)
This paper was presented at the American Economic Association meetings in Denver in September 1980. The research reported here is part of the NBER's research program in Economic Fluctuations. Any opinions expressed are those of the author and not those of the